Body dysmorphic disorder and nonweight‐related body image concerns in individuals with eating disorders. Issue 1 (9th October 2012) - Kollei, Ines; Schieber, Katharina; de Zwaan, Martina; Svitak, Michael; Martin, Alexandra
Abstract Objective: Research on the prevalence of body dysmorphic disorder (BDD) in individuals with eating disorders (EDs) is scarce. Nonweight‐related appearance concerns, which can be considered as variants of BDD concerns, have also rarely been examined in EDs. This study therefore investigates BDD prevalence and nonweight‐related appearance concerns in EDs. Method: One hundred individuals with EDs (49 inpatients with anorexia nervosa, 51 inpatients with bulimia nervosa) completed structured diagnostic interviews and self‐report questionnaires. Results: Twelve individuals with EDs (12.0%) suffered from comorbid BDD, with their body dysmorphic concerns being unrelated to weight and shape. BDD lifetime‐prevalence was 15.0%. There was a high prevalence of dissatisfaction with nonweight‐related body features such as skin, hair, teeth, nose, and height (20.8 to 53.5%). Discussion: Findings indicate that BDD is a frequent comorbid disorder in individuals with EDs. Furthermore, along with weight and body shape, nonweight‐related appearance concerns are also common in individuals with EDs. © 2012 by Wiley Periodicals, Inc. (Int J Eat Disord 2013)